Rancang Bangun Aplikasi Shift Piket Brimob Berbasis Web dan SMS Gateway - Nasution, Siti Aisyah; Arhami, Muhammad; Mulyadi, Mulyadi (Jurnal Teknologi Rekayasa Informasi dan Komputer, 2023)
Picket schedule information system is an important aspect to know each personnel's picket schedule. During this time picket schedule information still uses paper media. In Detachment B, Kompi 4 pioneers used the picket schedule manually. The purpose of designing this application is to create a system that can facilitate data processing and presentation of picket schedule information through the website so as to help Mobile Brigade personnel to obtain information easily. Not only from the web, the picket personnel also get information via sms. In addition, there are also printable reports that are used as a report on the implementation of pickets. The design of this application uses DFD, the tools used in making this system are the PHP programming language and the MySQL database for storing data, and the SMS gateway that is used as a reminder for the ticket schedule officer. The website generated from this research is a web-based picket schedule and sms gateway application Keywords: Shift, Mobile Brigade, SMS gateway, Web